2023
DOI: 10.3390/vetsci10020102
|View full text |Cite
|
Sign up to set email alerts
|

The Serological Response in Cattle following Administration of a Heterologous Sheep Pox Virus Strain Vaccine for Protection from Lumpy Skin Disease; Current Situation in Armenia

Abstract: Lumpy skin disease (LSD) is a highly infectious viral disease of cattle caused by LSD virus (LSDV), which was first reported in Armenia in late 2015. It was identified in pasture-raised cattle near the border with Iran. Currently, vaccination plays a key role in preventing further incursion of disease in high-risk areas. The purpose of this work was to assess the quality of vaccination currently used in Armenia by determining the immune response of the heterologous dry culture sheep pox virus-based vaccine aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Throughout the entire study period, all the cattle remained healthy in appearance with no obvious side effects in presentation or at the vaccine injection site. This is in concurrence with our previous study, which followed the same vaccination parameters and found there was no increase in body temperature or deviation from the physiological norm [32].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Throughout the entire study period, all the cattle remained healthy in appearance with no obvious side effects in presentation or at the vaccine injection site. This is in concurrence with our previous study, which followed the same vaccination parameters and found there was no increase in body temperature or deviation from the physiological norm [32].…”
Section: Resultssupporting
confidence: 93%
“…Veterinary authorities are presented with significant challenges when selecting effective vaccines due to the variability of testing, quality, efficacy, and affordability to farmers [22,34]. Since 2016, the Republic of Armenia has administered a heterologous sheep pox vaccine to protect cattle from LSDV [31,32,35], but the duration of immunity following vaccination with the heterologous vaccine was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Goran goat pox is able to protect cows from LSD. However, these results are different from a study conducted by Hakobyan et al (2023) that the heterologous vaccine (sheep poxvirus) used in Armenia provided immunity to the cattle population of 86.09% and did not cause any side effects in the cattle. Some of the factors identified as causing vaccine failure are differences between vaccine strains and virus strains that infect animals in the field, low vaccine titers, vaccination of animals that are temporarily experiencing an incubation period of disease, and errors in vaccine handling and storage (Datten et al, 2023).…”
Section: Prevention and Controlcontrasting
confidence: 99%